أسلوب التكرار ومثيراته الدلالية في شعر مصطفى صادق الرافعي قصيدة "الشرق المريض" نموذجاً (مجلة إحالات, 2025)
تحاول هذه الدراسة الكشف عن دقائق تقنية التكرار بوصفها ظاهرة موسيقية دلالية اتكئ عليها الشاعر مصطفى صادق الرافعي في شعره، وتحديداً في قصيدة "الشرق المريض"، خدمةً للفكرة النصية الرئيسية: "قضية المرأة الشرقية"، وفيها يسعى الرافعي إلى تصوير الشرق بوصفه امرأة، طوقتها الأمراض والأشجان والتي كان سببها ظلم الرجل لها، وطغيانه عليها بسلبها الإرادة وحق الاختيار والزواج ممن تحب ورفض من تكره. وقد ركزتْ هذه الدراسة على الغاية من التكرار وتعدد أشكاله في القصيدة، التي أسهمت في التعبير عن الحالة الشعورية التي كان الشاعر يكابدها المتمثلة في موقفه من مأساة المرأة داخل المجتمع العربي وما حلَّ بها من ويلات وظلمات، فكان البحث استنطاقاً لجماليات تقنية التكرار وسَبْر أغوراه البنائية. This study attempts to detect the minute technique of repetition as a phenomen on of musical semantic lean upon the poet Mustafa Sadiq Rafii in his hair, and specifically in the poem "company patient", the service idea text Key : "the case of oriental women", which seeks Rafii to portray the company as a woman, the collar of their diseases and visit the sacred and that was caused by the injustice of Man, and the tyranny of the US series will and right to choose and marry who you love and reject hate . And May this study focused on the end of the iteration and the modified forms in the poem, which have contributed to the expression of the emotional state that the poet was suffering of his attitude to the tragedy of women within the Arab society and what happened to him from the scourge and injustice, the decoder search inhalation of all operations of the refining technique and sounding more constructivism ..